Research and Discussion on the Relationships between Noise-Induced Hearing Loss and ATP2B2 Gene Polymorphism. (1st December 2019) - Zhang, Suhao; Ding, Enmin; Yin, Haoyang; Zhang, Hengdong; Zhu, Baoli
Abstract : Long-term and continuous noise exposure can result in noise-induced hearing loss (NIHL), which is a worldwide problem resulting from the interaction of environmental and genetic factors. The ATP2B2 gene polymorphism can destroy cochlear hair cells and increase the risk of NIHL. A case-control study of 760 Chinese textile workers was conducted to investigate the relationship between ATP2B2 polymorphisms and NIHL susceptibility. Venous blood was collected and questionnaires were conducted by professional physicians. A case group and a control group which were typed by individuals' pure-tone audiometry test results were set. Three polymorphism sites of ATP2B2 were genotyped by using the PCR technique. Analysis results revealed that the C allele of rs3209637 (95 % CI = 1.08 –2.58, odds ratio OR = 1.67, P = 0.027 ) was a dangerous factor and could add to risks of NIHL in the Chinese employees. The data of stratified analysis revealed that individuals who are exposed to noise > 95   dB with the rs3209637 C genotype have a higher susceptibility to NIHL (OR = 1.34, 95 % CI = 1.07 –1.68). Multifactor dimensionality reduction analysis revealed that the interaction between rs14154 and rs3209637 is linked to increased NIHL risk, and for the interaction among rs14154, smoking and drinking had the same function (OR = 1.54 and 1.77, 95 % CI = 1.15 –2.07, 1.33–2.37, and P = 0.0037 and P < 0.0001, respectively). Our results suggest that genetic polymorphism rs3209637 C within ATP2B2 is a risk factor for NIHL among Chinese employees and rs3209637 C could be a potential biomarker for NIHL patients.